Sox Genes Show Spatiotemporal Expression during Murine Tongue and Eyelid Development - Ryuichi Ishikawa; Maiko Kawasaki; Katsushige Kawasaki; Akane Yamada; Supaluk Trakanant; Fumiya Meguro; Atsushi Kitamura; Takehisa Kudo; Takeyasu Maeda; Atsushi Ohazama (International Journal of Dentistry)
The tongue is a critical organ, involved in functions such as speaking, swallowing, mastication, and degustation. Although Sox genes are known to play critical roles in many biological processes, including organogenesis, the expression of the Sox family members during tongue development remains unclear. We therefore performed a comparative in situ hybridization analysis of 17 Sox genes (Sox1–14, 17, 18, and 21) during murine tongue development. Sox2, 4, 6, 8, 9, 10, 11, 12, and 21 were found to be expressed in the tongue epithelium, whereas Sox2, 4–6, 8–11, 13, and 21 showed expression in the mesenchyme of the developing tongue. Expression of Sox1, 4, 6, 8–12, and 21 were observed in the developing tongue muscle. Sox5 and 13 showed expression only at E12, while Sox1 expression was observed only on E18. Sox6, 8, 9, and 12 showed expression at several stages. Although the expression of Sox2, 4, 10, 11, and 21 was detected during all the four stages of tongue development, their expression patterns differed among the stages. We thus identified a dynamic spatiotemporal expression pattern of the Sox genes during murine tongue development. To understand whether Sox genes are involved in the development of other craniofacial organs through similar roles to those in tongue development, we also examined the expression of Sox genes in eyelid primordia, which also contain epithelium, mesenchyme, and muscle. However, expression patterns and timing of Sox genes differed between tongue and eyelid development. Sox genes are thus related to organogenesis through different functions in each craniofacial organ.